Microwave-Assisted Synthesized Gadolinium Doped Barium Strontium Titanate Nanostructures: Structural and Optical Properties for DSSC Applications - Mayandi, Jeyanthinath (Malaysian NANO-An International Journal, 2021)
Gadolinium (Gd) doped barium strontium titanate (BST) was prepared using the microwave-assisted solid-state reaction method for dye sensitized solar cell (DSSC) applications. The optical properties and the structural analysis of the prepared samples reveal the optical band gap and the morphology. The XRD pattern of the annealed samples confirms the polycrystalline nature with the cubic crystal structure. When the dopant is added, the bandgap increases slightly from 3.11 to 3.27 eV. The J-V characteristics of DSSCs prepared with pure and doped BST were investigated. The efficiency of the DSSCs remained constant and there is a slight increase in the Jsc for highly doped samples under 1-sun illumination. Gadolinium doped barium strontium titanate shows variation in the J-V characteristics and could be a potential candidate for the solar photovoltaic applications.